MATHEMATICAL MODELLING AND EXPERIMENTAL INVESTIGATION OF MULTI-PASS SOLAR AIR HEATING COLLECTOR SYSTEM ASSISTED BY POROUS MATRIX - WASIU, KAREEM MORAKINYO (2017)
United Nations target of renewable energy demands improvement on the solar collector performance especially the solar air heating collector (SAHC) that has the least contribution to solar energy utilisation. Traditional open sun air (direct) drying is still popular with its shortcomings such as labour intensive and long drying time. Thrust of this research work has been to model and test the performance of a new multi-pass solar air heating collector (MPSAHC) system that stores sensible thermal energy in the porous matrix. The MPSAHC system heat energy balance has been analysed using finite difference approximation method while the gravimetric technique has been used to study the mass transfer of moisture from screw-pine (Pandanus tectorius) during drying operation under local weather condition of Seri Iskandar, Perak Malaysia. Laboratory experiments on the characterisation of porous matrices and oven drying operation using test chamber have been conducted. A series of outdoor tests have been planned and conducted for a period of 12 months. System temperature has been measured by sensors with uncertainty of 0:02, while other equipment used were calibrated with at least 95% level of confidence. A measure of relevant efficiencies has been determined from the data obtained during testing of the prototype. Integrated MPSAHC without traditional back insulation has achieved collector, exergy, pickup and drying efficiencies of 65%, 62